"Far North Features Pictured by the Bartlett-Academy of Natural Sciences Expedition to Greenland" (Philadelphia Evening Bulletin, 1930)
"Basaltic rock formation on Shannon Island, which, with Clavering Island, also off Greenland, was visited and explored by the expedition partly sponsored by the Academy of Natural Sciences." With clipping